The Share of Khadija Mastoor in Evolution of Urdu Novel: Zameen - Sarah Tariq (بازیافت, 2017)
Khadija Mastoor is an eminent novelist of progreesive era. She highlightes economic and social issues in her several short stories. She considerably added in the field of literature by writing novels Angan and Zameen that occupy their own comprehensive status. She presents Zameen. After the partition of sub-continent novel writing was badly effected by the brutality and oppusion of that age. Nearly every author wrote on this great tragedy of bloodshed of the sub continent. It was a sound of agitation and protest which was raised by the writer community. Zameen is an evident example of Khadija Mastoor's loyality with her mother land. Zameen is presentation of such characters who are indulged hankering wealth in a disgraceful manners after forgetting their past.This novel is a good piece of satire on those people who wanted to be so- called respectable mark of society after hoalding money from different means. Khadija Mastoor has critisized the ruler's outdated system.Her novel representes pakistani socio economic system. It is also a proof of the art and technique of Khadija Mastoor prose writing.